Institutional Effectiveness and Sustainability in Indian Higher Education: A Systematic Literature Review - Venkareddy, Chitkala (Journal of Neonatal Surgery, 2025)
India’s higher education system, ranking third globally in enrolment, has seen substantial growth in scale and institutional diversity. Despite this expansion, concerns about educational quality remain persistent and pressing. This study employs a Systematic Literature Review (SLR) to critically examine the multidimensional factors affecting quality and institutional effectiveness across Indian higher education institutions (HEIs). The analysis is guided by Zineldin’s 5Q Model, encompassing five core dimensions: object (curriculum and vision), process (teaching and assessment methods), infrastructure (physical and digital resources), interaction (student-faculty engagement), and atmosphere (institutional culture and governance climate). Drawing from 30 peer-reviewed studies, government policy documents, and accreditation reports published between 2010 and 2024, the review reveals systemic shortcomings across these five dimensions. Common issues include outdated curricula, fragmented regulatory structures, insufficient digital and physical infrastructure, low levels of faculty development, and weak student support systems. Furthermore, the study identifies emerging but underexplored concerns such as digital equity gaps, faculty burnout, and inadequate mental health support for students. While the National Education Policy (NEP) 2020 outlines progressive reforms, implementation remains uneven—especially in Tier 2 and 3 institutions. The findings emphasize the need for integrated and context-sensitive reforms. Enhancing quality requires more than compliance with external accreditation standards; it demands internalized, institution-wide commitment to continuous improvement, equity, and innovation. Recommendations include curriculum modernization, participatory governance, inclusive pedagogy, faculty capacity-building, and increased investment in smart infrastructure. This review provides a holistic framework for reimagining India’s higher education system in alignment with national aspirations and global benchmarks.